PENGARUH KECERDASAN EMOSIONAL DAN DUKUNGAN ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Leni Maryani; Sri Marten Yogaswara; Nur Azizah Hidayat (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to find out: (i) how emotional intelligence, parental support and student learning outcomes in economics class XI IIS SMAN 1 Padalarang, (ii) the effect of emotional intelligence on student learning outcomes in economics class XI IIS SMAN 1 Padalarang, (iii) the effect of parental support on student learning outcomes in economics class XI IIS SMAN 1 Padalarang, and (iv) the effect of emotional intelligence and parental support on student learning outcomes in economics class XI IIS SMAN 1 Padalarang. The research method used is a survey method with a quantitative approach and data collection techniques in the form of questionnaires and test questions. The results showed: (i) students' emotional intelligence was said to be very good with a score of 4.05, parental support in qualifications was very good with a score of 4.03 and student learning outcomes were categorized as sufficient with an average of 81.26 in the subject of income concept economics national class XI IIS SMAN 1 Padalarang, (ii) there is an effect of emotional intelligence of 42.5%, (iii) there is an influence of parental support of 31.5% (iv) there is an effect of emotional intelligence and parental support on student learning outcomes of 74%.